2022
DOI: 10.3390/foods11091357
|View full text |Cite
|
Sign up to set email alerts
|

Higher Yield and Polyphenol Content in Olive Pomace Extracts Using 2-Methyloxolane as Bio-Based Solvent

Abstract: Despite its severe toxicity and negative environmental impact, hexane remain the solvent of choice for the extraction of vegetable oils. This is in contrast with the constantly growing demand for sustainable and green extraction processes. In recent years a variety of alternatives to hexane have been reported, among them 2-methyloxolane (2-MeOx), which has emerged as a promising bio-based alternative. This study evaluates the possibility of replacing hexane, in the extraction of olive pomace (OP), with 2-MeOx,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Several studies have reported that 2-MeOx is also an efficient solvent for the extraction of phenolic compounds and yields polyphenol-rich extracts 41 with high antioxidant activity. 25,36,42 In this study, the oil obtained with 2-MeOx contained a significantly higher concentration (p < 0.05) of polyphenols than the oil obtained with hexane. The higher content of UM and phenolic compounds was probably the reason for the longer oxidative stability (induction time >70 h) compared to the hexane-extracted oil.…”
Section: Comparison Between 2-meox and Hexanementioning
confidence: 53%
See 2 more Smart Citations
“…Several studies have reported that 2-MeOx is also an efficient solvent for the extraction of phenolic compounds and yields polyphenol-rich extracts 41 with high antioxidant activity. 25,36,42 In this study, the oil obtained with 2-MeOx contained a significantly higher concentration (p < 0.05) of polyphenols than the oil obtained with hexane. The higher content of UM and phenolic compounds was probably the reason for the longer oxidative stability (induction time >70 h) compared to the hexane-extracted oil.…”
Section: Comparison Between 2-meox and Hexanementioning
confidence: 53%
“…Increasing the water content and thus the a w of the solvent favors the transfer of water from the solvent to the matrix, and the more hydrated wet meal retains more solvent, which increases the SRIs. Furthermore, this phenomenon causes swelling of the matrix, 36 which has a significant effect on the extraction kinetics. 25 These results provide a better understanding of the extraction process in its entirety and can be used to modulate water transfer between the matrix and the miscella.…”
Section: Optimization Of Extraction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-MeOx/H 2 O mixture (95.5/4.5% at 55 °C) must be fed to another distillation step to recover the dry 2-MeOx. However, studies have shown that 2-MeOx 95.5% can be used directly for oil extraction, showing a similar efficiency to the dry solvent [ 77 , 78 ]. Using COSMO-RS and Hansen solubility predictions, Sicaire et al [ 66 ] showed that 2-MeOx can be considered the best alternative to n -hexane among all solvents tested, as it can efficiently dissolve the desired compounds.…”
Section: Green Solvents’ Extractionmentioning
confidence: 99%
“…Hence, EVOO has the highest polyphenol content compared to refined olive oils, which is about 500 mg/L [ 43 , 44 ]. A remarkably high concentration of polyphenols and flavonoids was also reported in olive by-products, i.e., paste, pomace and aqueous extract [ 42 , 45 , 46 ]. Therefore, due to minimal processing, EVOO had higher levels of polyphenols and was more readily absorbed than refined olive oil [ 47 ].…”
Section: Olive Bioactive Compoundsmentioning
confidence: 99%